Molecular Features of the YAP Inhibitor Verteporfin: Synthesis of Hexasubstituted Dipyrrins as Potential Inhibitors of YAP/TAZ, the Downstream Effectors of the Hippo Pathway. (20th April 2017) - Gibault, Floriane; Bailly, Fabrice; Corvaisier, Matthieu; Coevoet, Mathilde; Huet, Guillemette; Melnyk, Patricia; Cotelle, Philippe
Abstract: Porphyrin derivatives, in particular verteporfin (VP), a photosensitizer initially designed for cancer therapy, have been identified as inhibitors of the YAP–TEAD interaction and transcriptional activity. Herein we report the efficient convergent synthesis of the dipyrrin half of protoporphyrin IX dimethyl ester (PPIX‐DME), in which the sensitive vinyl group was created at the final stage by a dehydroiodination reaction. Two other dipyrrin derivatives were synthesized, including dipyrrin19 [( Z )‐2‐((3, 5‐dimethyl‐4‐vinyl‐2 H ‐pyrrol‐2‐ylidene)methyl)‐3, 5‐dimethyl‐4‐vinyl‐1 H ‐pyrrole], containing two vinyl groups. We found that VP and dipyrrin19 showed significant inhibitory effects on TEAD transcriptional activity in MDA‐MB‐231 human breast cancer cells, whereas other compounds did not show significant changes. In addition, we observed a marked decrease in both YAP and TAZ levels following VP treatment, whereas dipyrrin19 treatment primarily decreased the levels of YAP and receptor kinase AXL, a downstream target of YAP. Together, our data suggest that, due to their chemical structures, porphyrin‐ and dipyrrin‐related derivatives can directly target YAP and/or TAZ proteins and inhibit TEAD transcriptional activity. Abstract : Directed dipyrrins : An efficient convergent synthesis yielded hexasubstituted dipyrrins structurally related to verteporfin (VP), with a sensitive vinyl group created at the final stage by a dehydroiodination reaction. While VP showed a direct effect on YAP and TAZ levels, one dipyrrin affected only YAP levels, suggesting that dipyrrin‐related compounds may directly affect the expression of YAP and/or TAZ.